2007
DOI: 10.1103/physrevlett.98.147001
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Scale Revival and Giant Kink in the Dispersion of a Cuprate Superconductor

Abstract: In the present photoemission study of a cuprate superconductor Bi1.74Pb0.38Sr1.88CuO6+delta, we discovered a large scale dispersion of the lowest band, which unexpectedly follows the band structure calculation very well. Similar behavior observed in blue bronze and the Mott insulator Ca2CuO2Cl2 suggests that the origin of hopping-dominated dispersion in an overdoped cuprate might be quite complicated. A giant kink in the dispersion is observed, and the complete self-energy containing all interaction informatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
63
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 29 publications
13
63
1
Order By: Relevance
“…They are in a good correspondence to experimental ARPES data. Indeed, in a wide area of frequencies a weak momentum dependence of spectrum along the nodal direction was found that is in agreement with experiment [11]. The spectral density turned out to be typical for strongly coherent excitations near the Fermi level in case of the strong electron-phonon binding.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They are in a good correspondence to experimental ARPES data. Indeed, in a wide area of frequencies a weak momentum dependence of spectrum along the nodal direction was found that is in agreement with experiment [11]. The spectral density turned out to be typical for strongly coherent excitations near the Fermi level in case of the strong electron-phonon binding.…”
Section: Discussionsupporting
confidence: 87%
“…It is a result of the appearance of polaron bands which are grouped near the frequencies to be multiple the phonon frequency ω 0 . It should be noted that there is a weak dependence of resonance frequency on k at g=0.06 (see Fig.17 a, curve 4) that is in agreement with ARPES experimental data [11]. The fine spectrum structure near the Fermi level shows an enough drastic frequency change with a small change of k. In particular, below the Fermi level the first kink is observed at Ω k ∼ −ω 0 , i.e.…”
Section: Influence Of the Electron-phonon Interaction On Electron supporting
confidence: 85%
See 1 more Smart Citation
“…It is well known that t ′ qualitatively changes the quasiparticle dispersion and mimics the differences between hole-and electron-doping in cuprates found using Hamiltonians which incorporate higher energy degrees of freedom 11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , cf. Fig.…”
Section: The 2d Hubbard Model Hamiltonian H H Ismentioning
confidence: 99%
“…The transfer of spectral weight from the low energy feature to higher energies occurs somewhere near the middle of the (π, π) to Γ cut. Quite recently, similar behavior has been also found in doped compounds [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 53%